Growth and adjustment in national agricultures : four case studies and an overview - O'Hagan, J. P.; Food and Agriculture Organization of the United Nations (London : Macmillan : published by arrangement with the Food and Agriculture Organization of the United Nations, 1978)
This book deals with rapid changes in agriculture, The traditional techniques been confronted by new social requirement and technological possibilities.
Includes index.
Includes bibliographical references: p. 237-238.
oo 16/01/2019
Loans
Keywords: Agriculture